2013
DOI: 10.1007/s11064-013-1214-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Mannose-Binding Lectin Levels and Acute Ischemic Stroke Risk

Abstract: Complement activation and inflammation have been suggested in the pathogenesis of stroke, mannose-binding lectin (MBL) were found to have roles during the process. The aim of this study was to investigate the relationship between acute ischemic stroke (AIS) and serum MBL levels in Chinese population. From January 1 to June 30 2013, all patients with first-ever AIS were recruited to participate in the study. Serum MBL levels and routine test were examined. The National Institutes of Health Stroke Scale (NIHSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…An independent association between variant MBL2 genotypes and coronary artery disease (CAD) was previously confirmed in the American Indian, Strong Heart Study (SHS) cohort (OR = 3.2, 95% CI 1.5-7.0, p =0.004, adjusted for 11 CAD covariates) [31]. Osthoff et al [32] reported that MBL deficiency is associated with smaller cerebral infarcts and favorable outcome in ischemic stroke patients receiving conservative treatment, while Wang et al [33] found that elevated MBL levels could be considered as an independent stroke risk factor, suggesting a role of MBL and the lectin pathway of complement activation in the pathogenesis of stroke.…”
Section: Discussionmentioning
confidence: 90%
“…An independent association between variant MBL2 genotypes and coronary artery disease (CAD) was previously confirmed in the American Indian, Strong Heart Study (SHS) cohort (OR = 3.2, 95% CI 1.5-7.0, p =0.004, adjusted for 11 CAD covariates) [31]. Osthoff et al [32] reported that MBL deficiency is associated with smaller cerebral infarcts and favorable outcome in ischemic stroke patients receiving conservative treatment, while Wang et al [33] found that elevated MBL levels could be considered as an independent stroke risk factor, suggesting a role of MBL and the lectin pathway of complement activation in the pathogenesis of stroke.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent clinical study Wang et al [55] assessed serum levels of MBL in 148 Chinese patients with acute ischaemic stroke (the blood samples were obtained within 24 hours from recognition). MBL levels were significantly higher in stroke patients compared with healthy controls and increased with increasing severity of stroke.…”
Section: Mbl In Injury To Peripheral Organsmentioning
confidence: 99%
“…In the case of tissue damage, MBL rapidly deposits on target cells and triggers downstream complement activation in the acute phase, enhancing the cleavage of C3 (9). In patients in the acute phase of the stroke, MBL seems to contribute to inflammatory cerebral injury as well as to play a direct role in stroke recovery (10,11). Furthermore, several studies in animal models have shown that MBL-mRNA is expressed in brain tissue (12) and the lectin pathway is central to the propagation of ischemia-reperfusion injury across a variety of tissues (13,14).…”
mentioning
confidence: 99%